2014
DOI: 10.1111/evj.12267_76
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel High‐Sensitivity Cardiac Troponin‐T Assay in Horses

Abstract: This publication is a compilation of all Research Abstracts presented at the Ninth International Conference on Equine Exercise Physiology. Unlike previous ICEEP conferences there will not be a conference proceedings of full length manuscripts. These abstracts succinctly summarise a wide array of investigations relevant to the equine athlete, and will be useful to veterinarians and others involved in management of horses used for sport, work and competition. The abstracts encompass the topics of Applied Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several studies presented at ICEEP 9 focused on the cardiovascular system, including 2 describing measurement of cardiac troponin T (cTnT) in horses . Previous studies of athletic horses have largely focused on measurement of cardiac troponin I (cTnI), a myocardial polypeptide which can be measured in equine plasma as a sensitive biomarker of cardiac tissue injury .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies presented at ICEEP 9 focused on the cardiovascular system, including 2 describing measurement of cardiac troponin T (cTnT) in horses . Previous studies of athletic horses have largely focused on measurement of cardiac troponin I (cTnI), a myocardial polypeptide which can be measured in equine plasma as a sensitive biomarker of cardiac tissue injury .…”
mentioning
confidence: 99%
“…Plasma cTnI concentrations in horses can increase after prolonged endurance exercise or after brief, intense exercise, without clinical indications of cardiac disease . At ICEEP 9 , a group of investigators presented work in which they validated a high sensitivity cTnT using plasma samples from 120 horses of 5 different breeds . Results suggested that the majority of healthy sedentary horses would have cTnT concentrations below the detection limit of the assay, which has some repercussions regarding its use.…”
mentioning
confidence: 99%